The statistical model of mechanical milking duration of farmyard milking installation - Кучерук, Володимир Юрійович; Паламарчук, Євген Анатолійович; Кулаков, Павло Ігорович; Гнесь, Тетяна Вікторівна (Eastern-European Journal of Enterprise Technologies, 2014)
Based on the conducted theoretical studies, a statistical model that establishes the functional relationship between statistical characteristics of the milking duration of the farmyard milking installation for animal tied housing and statistical characteristics of the animal preparation time, statistical properties of the milking time, number of animals, number of milking machines, type of milking machine was developed. The model takes into account the use of milking machines with the milking process control function and milking machines without this function. The developed statistical model of the milking duration of the farmyard milking installation will allow to improve the accuracy of determining the productivity of the milking installation in its designing or upgrading, develop a methodology for designing data-measuring systems of parameters of technological processes of milking and dairy rooms and automatic control systems of livestock farms. The results of the theoretical studies were proved by the experimental data. The discrepancy between experimental results and theoretical calculations does not exceed 12% that indicates the adequacy of the developed model.